CORRELATION BETWEEN AUTHORITARIAN PARENTING AND DATING VIOLENCE OF STUDENTS IN PEKANBARU - Edwy, Veronica Kharisma; Zulian Fikry (Causalita, 2025)
Dating violence or dating violence is a form of behavior that is hurtful or abusive towards a partner in a relationship carried out by one of the parties and the victim of this violence feels physically and mentally injured. One factor that triggers dating violence is family history, where the perpetrator who commits violence has witnessed violence perpetrated by their parents. Authoritarian parenting has an impact on adolescent behavior in committing dating violence. Lack of open communication and overt models of aggression can influence adolescents to imitate these patterns in dating relationships. The aim of this research is to determine the relationship between Authoritarian Parenting Patterns and dating violence among students in Pekanbaru with quantitative research methods. The number of samples used in this research was 315 samples using a purposive sampling technique. Based on the analysis results, the correlation coefficient value was 0.391 with a value of (p > 0.05). These results show that there is a significant correlation between Authoritarian Parenting Patterns and Dating Violence among Pekanbaru students. This means that the higher the Authoritarian Parenting Pattern, the higher the Dating Violence, conversely, the lower the Authoritarian Parenting Pattern, the lower the Dating Violence among Pekanbaru Riau students.